The American dream in Vietnamese - Lieu, Nhi T. (University of Minnesota Press, 2011)
In her research on popular culture of the Vietnamese diaspora, Nhi T. Lieu explores how people displaced by war reconstruct cultural identity in the aftermath of migration. Embracing American democratic ideals and consumer capitalism prior to arriving in the United States, postwar Vietnamese refugees endeavored to assimilate and live the American Dream. In "The American Dream in Vietnamese," she claims that nowhere are these fantasies played out more vividly than in the Vietnamese American entertainment industry. Lieu examines how live music variety shows and videos, beauty pageants.